IMPLEMENTATION OF RELIGIOUS MODERATION THROUGH LOCAL WISDOM OF MUSLIM AND CONFUCIAN COMMUNITIES IN BAGAN SIAPIAPI, ROKAN HILIR DISTRICT, RIAU PROVINCE - Ahmad Fauzi, Afrinaldy Rustam, Darmawan Tia Indrajaya, Achmad Ghozali Syafi’i, Kemas Muhammad Gemila (JADID: Journal of Quranic Studies and Islamic Communication, 2025)
This study aims to explain the implementation of religious moderation through local wisdom in Muslim and Confucian communities in Bagan Siapiapi, Rokan Hilir Regency, Riau. Religious moderation is important in the context of pluralism to encourage religious harmony and tolerance. In this research, emphasis is given to the Muslim and Confucian communities as a representation of the two religions that exist in the region. This research uses a qualitative approach through a case study with the population including Muslim and Confucian communities in Bagan Siapiapi. The sample used was purposive sampling with a number of respondents reflecting social and religious variations. Data were collected through in-depth interviews and participatory observation. The results of this study show that the implementation of religious moderation through local wisdom in Bagan Siapiapi is carried out through a number of concrete practices reflected in tolerance towards other religious groups, participation in interfaith activities, and recognition of universal human values. In the Confucian community, it is reflected in the spirit of interfaith dialogue, respect for local culture, and cooperation with the Muslim community in social activities. However, this study also identified some challenges in the implementation of religious moderation, such as economic uncertainty, negative perceptions of other religions, and a lack of in-depth understanding of the principles of religious moderation. continued,